A bibliometric analysis: Ca2+ fluxes and inflammatory phenotyping by flow cytometry in peripheral blood mononuclear cells - Brun, Camille; Chalet, Lucie; Moulin, Florentin; Bochaton, Thomas; Ducreux, Sylvie; Paillard, Melanie; Crola Da Silva, Claire (Frontiers in Immunology, 2023)
The immune system, composed of organs, tissues, cells, and proteins, is the key to protecting the body from external biological attacks and inflammation. The latter occurs in several pathologies, such as cancers, type 1 diabetes, and human immunodeficiency virus infection. Immunophenotyping by flow cytometry is the method of choice for diagnosing these pathologies. Under inflammatory conditions, the peripheral blood mononuclear cells (PBMCs) are partially activated and generate intracellular pathways involving Ca2+-dependent signaling cascades leading to transcription factor expression. Ca2+ signaling is typically studied by microscopy in cell lines but can present some limitations to explore human PBMCs, where flow cytometry can be a good alternative. In this review, we dived into the research field of inflammation and Ca2+ signaling in PBMCs. We aimed to investigate the structure and evolution of this field in a physio-pathological context, and then we focused our review on flow cytometry analysis of Ca2+ fluxes in PBMCs. From 1984 to 2022, 3865 articles on inflammation and Ca2+ signaling in PBMCs were published, according to The Clarivate Web of Science (WOS) database used in this review. A bibliometric study was designed for this collection and consisted of a co-citation and bibliographic coupling analysis. The co-citation analysis was performed on 133 articles: 4 clusters highlighted the global context of Ca2+ homeostasis, including chemical probe development, identification of the leading players in Ca2+ signaling, and the link with chemokine production in immune cell function. Next, the bibliographic coupling analysis combined 998 articles in 8 clusters. This analysis outlined the mechanisms of PBMC activation, from signal integration to cellular response. Further explorations of the bibliographic coupling network, focusing on flow cytometry, revealed 21 articles measuring cytosolic Ca2+ in PBMCs, with only 5 since 2016. This final query showed that Ca2+ signaling analysis in human PBMCs using flow cytometry is still underdeveloped and investigates mainly the cytosolic Ca2+ compartment. Our review uncovers remaining knowledge gaps of intracellular players involved in Ca2+ signaling in PBMCs, such as reticulum and mitochondria, and presents flow cytometry as a solid option to supplement gold-standard microscopy studies.